2010
DOI: 10.1083/jcb.201002055
|View full text |Cite
|
Sign up to set email alerts
|

The mitosis-to-interphase transition is coordinated by cross talk between the SIN and MOR pathways in Schizosaccharomyces pombe

Abstract: The SIN pathway blocks inappropriate actin rearrangements during cytokinesis by preventing activation of the MOR pathway component Orb6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 50 publications
7
76
1
Order By: Relevance
“…In S. pombe, the NDR-family kinase Mob2p-Orb6p (Hou et al 2003) is a component of the morphology network (MOR), which regulates polar growth in S. pombe. It has been suggested that increased SIN activity is antagonistic to the MOR (Ray et al 2010), and that SIN activity in mitosis turns off polar growth in preparation for cytokinesis; reviewed by Gupta and McCollum (2011). It is therefore possible that the morphology problems observed in the ypa2-D mutant may result from increased SIN activity, a direct effect upon the MOR, or a combination of these.…”
Section: Pp2a and Sin Signalingmentioning
confidence: 99%
“…In S. pombe, the NDR-family kinase Mob2p-Orb6p (Hou et al 2003) is a component of the morphology network (MOR), which regulates polar growth in S. pombe. It has been suggested that increased SIN activity is antagonistic to the MOR (Ray et al 2010), and that SIN activity in mitosis turns off polar growth in preparation for cytokinesis; reviewed by Gupta and McCollum (2011). It is therefore possible that the morphology problems observed in the ypa2-D mutant may result from increased SIN activity, a direct effect upon the MOR, or a combination of these.…”
Section: Pp2a and Sin Signalingmentioning
confidence: 99%
“…Pmo25p, Nak1p and Sog2p localise to the SPB and the division site, whereas Mob2p, Orb6p and Mor2p only localise to the cell periphery and the division site. Orb6p and Nak1p activity is high in interphase and decreases during mitosis, when tip growth ceases (Kanai et al, 2005;Mendoza et al, 2005;Ray et al, 2010).…”
Section: Targets Of Sid2p In the Car Checkpointmentioning
confidence: 99%
“…Important for CAR assembly. Control of polarized growth Nak1p and Sog2p Gupta et al, 2014;Gupta et al, 2013;Ray et al, 2010 Proposed mutual inhibition between SIN and MOR prevents conflicts between polar growth and cytokinesis.…”
Section: Turning the Sin Offmentioning
confidence: 99%
“…However, there is no indication that significant numbers of dma1-D spores undergo inappropriate septation during the germination process (Krapp et al, 2010). Alternatively, the SIN might be silenced to prevent it from inhibiting the morphology network, which is required to establish polar growth (Gupta et al, 2013;Ray et al, 2010), in the germinating apolar spore. It is noteworthy that dma1-D spores are slow to germinate and resume polar growth (Krapp et al, 2010).…”
Section: Discussionmentioning
confidence: 99%